Penerapan metode forward chaining dan certainty factor untuk mengetahui gangguan mental pada remaja - Hafizhah Mardivta (Computer Science and Information Technology, 2024)
Mental disorders are a condition where people have mental, social, growth and development problems or disorders that hinder their life processes and interactions with other people. Mental health can be influenced by several factors, for example friendships, family, lifestyle, and many other factors. Many people do not want to undergo mental examinations from psychologists due to several factors, namely people feel embarrassed and afraid to talk about their problems, lack of knowledge of the symptoms and types of mental disorders, and fear of the surrounding environment. One way to help overcome this problem is to use an expert system. This expert system was built to determine mental disorders in adolescents using the Forward Chaining and Certainty Factor methods. The Forward Chaining method will be collaborated with the Certainty Factor method to calculate the level of accuracy of the type of mental disorder experienced. The use of these two methods aims to provide better results in identifying mental disorders in adolescents. The data taken in this research is data on mental disorders at the UPI YPTK Psychology Institute. The data used consists of 50 symptom data and 7 disease data. The results of this research are an Expert System application using the PHP programming language which is used to determine mental disorders in adolescents. From the tests that have been carried out, results were obtained with an accuracy level of 0.9998%. Expert system applications can be used for early action in preventing mental disorders in adolescents.